2019
DOI: 10.1016/j.cub.2019.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Effects of UVA on Arabidopsis Are Mediated by a Novel cGMP Phosphodiesterase

Abstract: Summary Although UVA radiation (315–400 nm) represents 95% of the UV radiation reaching the earth’s surface, surprisingly little is known about its effects on plants [ 1 ]. We show that in Arabidopsis , short-term exposure to UVA inhibits the opening of stomata, and this requires a reduction in the cytosolic level of cGMP. This process is independent of UVR8, the UVB receptor. A cGMP-activated phosphodiesterase ( AtCN-PDE1 ) was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…In the short term, plants respond to drought by the influence of stomatal movement on stomatal aperture. For example, stomata open and close, which is mainly regulated by the levels of hormone ABA (He et al, 2018; Li, Han, Su, Guo, & Zhang, 2019; J Li et al, 2017; S. Qi et al, 2019; J. Wang et al, 2018), light (Isner et al, 2019) and nutrient conditions (Schaefer et al, 2018). During evolution, plants adapt to a drought environment by changing stomatal traits, such as stomatal size and stomatal density (Bertolino, Caine, & Gray, 2019; Dow, Bergmann, & Berry, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the short term, plants respond to drought by the influence of stomatal movement on stomatal aperture. For example, stomata open and close, which is mainly regulated by the levels of hormone ABA (He et al, 2018; Li, Han, Su, Guo, & Zhang, 2019; J Li et al, 2017; S. Qi et al, 2019; J. Wang et al, 2018), light (Isner et al, 2019) and nutrient conditions (Schaefer et al, 2018). During evolution, plants adapt to a drought environment by changing stomatal traits, such as stomatal size and stomatal density (Bertolino, Caine, & Gray, 2019; Dow, Bergmann, & Berry, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the well-reported effects of UV-B light, much less is known about the roles of UV-A radiation (315-400 nm) on stomatal movement. Recently, it was shown that Arabidopsis epidermis illuminated with UV-A in combination with blue and red light demonstrated greatly decreased stomatal aperture than those illuminated with only blue and red light, and that the effect was strong at 3 h post exposure and decreases with time (Isner et al, 2019). It is noted that UV-A irradiation could not trigger closure in stomata that had previously been opened by blue and red light illumination.…”
Section: Ultraviolet Light Signaling Inhibits Blue and Red Light-indumentioning
confidence: 99%
“…Taken together, UV-B and UV-A light signaling acts in concert to limit stomatal opening in periods of strong solar irradiance. Although it was shown that the photoreceptor UVR8 mediates the perception of both UV-B and UV-A wavelengths (Rai et al, 2020), UV-A-mediated stomatal closure does not require UVR8 (Isner et al, 2019). Considering that CRY1 and CRY2 also act as photoreceptors for UVA radiation (Lin et al, 1995), further studies are needed to elucidate how CRY1/2 integrate blue and UV-A light signals to regulate stomatal responses and how decreased cGMP levels mediate the inhibition of blue/red light-induced stomatal opening.…”
Section: Ultraviolet Light Signaling Inhibits Blue and Red Light-indumentioning
confidence: 99%
“…However, the molecular mechanisms of cGMP signal transduction to cellular effectors, including cGMP-dependent kinases G, are still poorly characterized (Świeżawska et al, 2018). Recent reports described the identification of cGMPdependent protein kinase with a role in mediating gibberellin responses in rice (Shen et al, 2019) and a plant cGMPactivated phosphodiesterase involved in the UVA-induced cGMP degradation in Arabidopsis stomata (Isner et al, 2019). Signaling pathways involved in the regulation of stomatal movements by external stimuli and phytohormones comprise, beside cGMP, diverse components like NO, ROS, cytosolic pH, calcium ions and phospholipids (Daszkowska-Golec and Szarejko, 2013;Gayatri et al, 2013;Agurla et al, 2014;Agurla and Raghavendra, 2016).…”
Section: Biological Functions In Plantsmentioning
confidence: 99%